STRATEGI GURU DALAM MENGGUNAKAN BAHASA IBU (MOTHER TONGUE) UNTUK MENDUKUNG PEMBELAJARAN SISWA DI SD NEGERI 006 ROKAN IV KOTO - Ananda, Rizki; Rahma Putri, Auliya; Nupus, Hayatun; Mardhotillah Nasmai, Ledy; Fadhilla, Rahmah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to explore the strategies used by teachers in utilizing the mother tongue in the learning process in the first-grade classes at SD Negeri 006 Rokan IV Koto. The approach used is qualitative with a case study design. Data were collected through in-depth interviews, participatory observations, and documentation. The results indicate that the use of the mother tongue in the first-grade classes at SD Negeri 006 Rokan IV Koto helps students better understand the material, increases class participation, and strengthens the emotional connection between the teacher and students. The strategies implemented include translanguaging, the use of local metaphors, and strengthening concepts through contextual dialogue. This study recommends teacher training on the effective use of the mother tongue in the learning process.